2022
DOI: 10.2147/tcrm.s354695
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Olfactory Nerve Regeneration Mechanism and Olfactory Training

et al.

Abstract: The olfactory nerve (ON) is the only cranial nerve exposed to the external environment. Hence, it is susceptible to damage from head trauma, viral infection, inflammatory stimulation, and chemical toxins, which can lead to olfactory dysfunction. However, compared with all other cranial nerves, the ON is unique due to its inherent ability to regenerate. This characteristic provides a theoretical basis for treatment of olfactory dysfunction. Olfactory training (OT) is one of the main treatments for olfactory dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 87 publications
(81 reference statements)
0
8
0
Order By: Relevance
“…Although olfaction in humans is less appreciated than other senses, it affects our lives all the time ( 23 ). Because the olfactory nerve is the cranial nerve exposed to the external environment, it is vulnerable to tumor compression and inflammatory stimulation, resulting in reduced olfactory function ( 24 ). Olfactory nerve injury cannot be recovered if there is a prolonged attack of the lesion and the degree of damage is relatively severe ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although olfaction in humans is less appreciated than other senses, it affects our lives all the time ( 23 ). Because the olfactory nerve is the cranial nerve exposed to the external environment, it is vulnerable to tumor compression and inflammatory stimulation, resulting in reduced olfactory function ( 24 ). Olfactory nerve injury cannot be recovered if there is a prolonged attack of the lesion and the degree of damage is relatively severe ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only Altundag et al reported the effectiveness of a modified OT protocol on COVID-19 patients with parosmia but this profile of patients differed from ours (hyposmia–anosmia patients). From a pathophysiological standpoint, the repeated short-term exposure to odors may increase both the growth of olfactory receptor neurons and the expression of olfactory receptor in the olfactory cleft mucosa [ 9 , 19 ]. The positive influence of OT may also involve olfactory bulb and brain changes [ 9 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Albers [9] also pointed out that the common causes of OD were upper respiratory tract infections, head trauma, and nasal inflammatory diseases. Moreover, the nasal olfactory mucosa contains olfactory nerves, which are the main sites of primary olfactory smell and easily harmed [10]. Thus, nasal diseases have been recognized to substantially affect the olfaction.…”
Section: Introductionmentioning
confidence: 99%